DIFFICULTIES IN THE APPLICATION OF INTERACTIVE TEACHING METHODS - Olga V. Lomakina (Высшее образование в России, 2016)
The article is an attempt to analyze the difficulties in the use of interactive methods in the educational process from the positions of teachers and students.